Fecal transplant modifies urine chemistry risk factors for urinary stone disease. Issue 4 (21st February 2019) - Stern, Joshua M.; Urban‐Maldonado, Marcia; Usyk, Mykhaylo; Granja, Ignacio; Schoenfeld, Daniel; Davies, Kelvin P.; Agalliu, Ilir; Asplin, John; Burk, Robert; Suadicani, Sylvia O.
Abstract: Urinary stone disease (USD) is a major health concern. There is a need for new treatment modalities. Recently, our group provided evidence for an association between the GMB composition and USD. The accessibility of the Gut Microbiome (GMB) makes it an attractive target for investigation and therefore, in these studies we have evaluated the extent to which the whole gut microbial community in fecal transplants can affect urinary stone risk parameters in an animal model. Fresh fecal pellets were collected from Zucker lean rats, homogenized in PBS (100 mg/mL), filtered through a 70  μ m strainer and then orally gavaged into C57BL/6NTac germ‐free mice. Twenty‐four hours urine collections and GMB analysis were performed over time for 1 month. Kidney and gut tissue were harvested from transplanted mice for western blot analysis of expression levels of the Slc26a6 transporter involved in oxalate balance. Urinary calcium decreased after fecal transplant by 55% ( P  < 0.001). Urinary oxalate levels were on average 24% lower than baseline levels ( P  < 0.001). Clostridiaceae family was negatively correlated with urinary oxalate at 4 weeks after transplant ( r  = −0.83, P  < 0.01). There was a 0.6 unit average increase in urinary pH from a baseline of 5.85 (SE ± 0.028) to 6.49 (SE ± 0.04) ( P  < 0.001) after transplant. There was a concomitant 29% increase in gastrointestinal alkali absorption ( P  < 0.001) 4‐weeks after fecal transplant. Slc26a6 expression increased by 90% in the cecum after transplant. Our results suggest that the gut microbiome may impact metabolism, alters urinary chemistry, and thereby may influence USD; the accessibility of the GMB can potentially be leveraged for therapeutic interventions. Abstract : This paper represents a very early publication in this field of urology suggesting that the GMB can alter urinary stone parameters important for stone risk.